The Place Where You Go to Listen: In Search of an Ecology of Music - Adams, John Luther 1953- (Middletown, WI Wesleyan University Press, 2009)
Did Alaska create the music of John Luther Adams, or did the music create his Alaska? For the past thirty years, the vastness of Alaska has swept through the distant reaches of the composers imagination and every corner of his compositions. In this new book Adams proposes an ideal of musical ecology, the philosophical foundation on which his largest, most complex musical work is based. This installation, also called The Place Where You Go to Listen, is a sound and light environment that gives voice to the cycles of sunlight and darkness, the phases of the moon, the seismic rhythms of the earth, and the dance of the aurora borealis. Adams describes this work as a place for hearing the unheard music of the world around us. The book includes two seminal essays, the composers journal telling the story of the day-to-day emergence of The Place, as well as musical notations, graphs and illustrations of geophysical phenomena.
Keywords: art philosophy & esthetics; Philosophy